Integrating music and movement with literacy - Morgan, Nancy Battista; Educational Activities Video; KNB Production (Baldwin, N.Y. : Educational Activities Video, 2004)
This video program and accompanying leader's guide will give teachers, aides and other staff the skills to help their preschool through first grade students develop many literacy skills by using music and movement as a vehicle of instruction
Title from title screen
Music specialist, Carole Peterson ; teacher, Sue Curtin
Narrator: Ana Maria Alvarez
Keywords: Early childhood education; Music -- Study and teaching; Movement education